1999
DOI: 10.1037/1076-8998.4.3.207
|View full text |Cite
|
Sign up to set email alerts
|

A process model of shiftwork and health.

Abstract: The authors developed and tested a process model of adaptation to shiftwork, which hypothesizes that various individual and situational variables influence the development of sleep and social and domestic disturbances. Both types of disturbances trigger various types of coping behavior, leading to several proximal outcomes. The end result is the development of chronic health problems in the form of digestive and cardiovascular symptoms. The model was tested with survey data collected from 2 samples of nurses (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
2
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 25 publications
(30 reference statements)
2
63
2
4
Order By: Relevance
“…In a large-scale study of nurses and industrial workers, morningness did not predict sleep or social/domestic disturbance (Smith et al, 1999). Di Milia and Muller (2012) showed that MT shift workers were significantly more alert during the morning hours but this pattern changed in the evening/night hours when ET were more alert.…”
Section: Adjustement To Shift Work and Jet Lagmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large-scale study of nurses and industrial workers, morningness did not predict sleep or social/domestic disturbance (Smith et al, 1999). Di Milia and Muller (2012) showed that MT shift workers were significantly more alert during the morning hours but this pattern changed in the evening/night hours when ET were more alert.…”
Section: Adjustement To Shift Work and Jet Lagmentioning
confidence: 99%
“…Smith et al (1999) reported that irrespective of the actual shift schedule parameters and type of job, workers with inflexible sleeping habits had greater sleep disturbances and in turn resulted in increased fatigue and emotional disturbances. Furnham and Hughes (1999) found journalists with flexible sleeping habits were better able to overcome drowsiness and had greater well-being.…”
Section: Adjustement To Shift Work and Jet Lagmentioning
confidence: 99%
“…They provide some evidence of the impact of night work on physical and psychological well-being, although it should be noted that most studies have provided data regarding reactions to night work within the context of a single nation. 3,4,8,9,10 For example, in a longitudinal study of Australian student nurses, Bohle and Tilley reported a negative effect on psychological well-being when student nurses moved from a day shift to a night shift; they found that night work was a significant predictor of a variety of psychological symptoms. 4 More recently, using data from one nation that was gathered as part of a five nation study, Kaliterna et al 4 found that night shift workers in the health care professions reported being more physically tired at the end of their workday than did non-night workers.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,5,8,12,16,19,23 In the frame of the stress-strain model, they emphasise both occupational and non-occupational stressors, as well as cognitive and behavioural coping efforts and strategies: some models focus more on personal aspects, others deal more with organisational and social conditions.…”
Section: Several Models and Methods Of Health Assessment And Preventionmentioning
confidence: 99%